Role of Endogenous Hormones on Seed Hardness in Pomegranate Fruit Development - Haoxian Li; Lina Chen; Ruitao Liu; Zhenhua Lu (Horticulturae)
Seed hardness is a unique trait for edibility and an important breeding target for pomegranates. We compared changes in hormones during the development of soft- and hard-seeded varieties in order to identify key hormones and developmental stages that affect seed lignin synthesis and accumulation. During the development of pomegranate seeds, lignin accumulates significantly in the stereid layer, and the degree of lignification is higher in Shandazi than in Huazi cultivars. The results showed that the accumulation of lignin in the stereid layer of the outer pomegranate seed coat is the reason for the differences in seed hardness between the soft-seeded variety and the hard-seeded variety. The hardness of pomegranate seeds was positively correlated with endogenous indole-3-acetic acid (IAA) and jasmonic acid (JA), while it was negatively correlated with cytokinins (CTKs), abscisic acid (ABA), gibberellins (GAs), salicylic acid (SA), and strigolactones (SLs). The highest contents of IAA and JA were 8.615 ng·g−1 and 4.5869 ng·g−1, respectively, in the hard-seeded variety. In the soft-seeded variety, the maximum values of dihydrozeatin (DZ), dihydrozeatin-7-glucoside (DHZ7G), ABA, gibberellin A1 (GA1), SA, and 5-deoxystrigol (5-DS) were 281.82 ng·g−1, 1542.889 ng·g−1, 61.273 ng·g−1, 5.2556 ng·g−1, 21.15 ng·g−1, and 0.4494 ng·g−1, respectively. IAA, CTKs, ABA, GA1, and SA play major roles in the formation of lignin in pomegranate seeds, collectively determining seed hardness.